I've successfully proven $A(x,y)$ for some fixed x and any y with induction but I'm having a hard time proving this for any x and y. I think the next useful step would be proving $A(x,0)= 2[x]3-3 $ but I still having trouble proving it... The definition of $A(x,y)=$ $$\begin{eqnarray*} A(0,y) &=& y+1 \\ A(x+1,0) &=& A(x,1) \\ A(x+1,y+1) &=& A(x,A(x+1,y)) \end{eqnarray*}$$

  • Perhaps you should give the definition of $A$, because there are many slightly different definitions... – Xoff Dec 20 '15 at 11:31
up vote 1 down vote accepted

First, you may see that for all $x$, $2[x]2=4$ for all $x>0$

For $x=0$ $$2[0](y+3 )-3=y+4-3=y+1=A(0,y)$$

Now, by induction on $x$, I suppose this is true for $x$ : $A(x,y)=2[x](y+3 )-3$

For $x+1$

$$A(x+1,0)=A(x,1)=2[x]4-3=2[x](2[x]2)-3=2[x+1]3-3$$

(This is also true when $x=0$, because $A(1,0)=2=5-3=2[1]3-3$)

Now by induction on $y$ :

\begin{align} A(x+1,y+1)&=A(x,A(x+1,y))\\ &=2[x]\bigl(2[x+1](y+3 )-3+3\bigr)-3\\ &=2[x]\bigl(2[x+1](y+3 )\bigr)-3\\ &=2[x+1](y+4 )-3\\ \end{align}

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.